Rare‐Earth Doped ZnO Films: A Material Platform to Realize Multicolor and Near‐Infrared Electroluminescence. Issue 3 (2nd January 2014) - Yang, Yang; Li, Yunpeng; Wang, Canxing; Zhu, Chen; Lv, Chunyan; Ma, Xiangyang; Yang, Deren
<x xml:space="preserve">Abstract</x> Light‐emitting devices based on MgxZn1‐xO/ZnO:RE/Si heterostructures are proposed. Hot holes formed in MgxZn1‐xO layers enter into ZnO:RE layers to impact‐excite the RE3+ ions therein. From the devices using ZnO:RE (Eu, Er and Tm) films, electroluminescence in red, green, blue, and also optical‐communication wavelengths are achieved. Such RE‐related electroluminescence can be activated by extraordinarily low voltages of only several volts. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>